PROGRAM LAKAMOLA ANAN SIO DI KABUPATEN ROTE NDAO (STUDI TENTANG DALAM PEMBERDAYAAN EKONOMI MASYARAKAT DI DESA TUALIMA KABUPATEN ROTE NDAO) - Jihan Marta Patola; Esrah D.N.A. Benu; Diana S.A.N. Tabun (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to analyze the implementation of the Lakamola Anan Sio Program and its impact on community economic empowerment in Tualima Village, Rote Ndao Regency. This research uses a qualitative approach with data collection techniques including interviews, observation, and documentation. The results show that the program has a positive impact on increasing community income, diversifying livelihoods, and strengthening farmer groups. However, several challenges remain, such as limited access to capital, lack of skills training, and suboptimal product marketing. Therefore, stronger coordination between government and community is needed to ensure sustainability.